Of Pins and Beads: Note on a Feminine Costume in Mari - Couturaud, Barbara (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
In the spring of 1965, in one of the rooms of the third millennium palace of Mari, André Parrot exhumed a jar containing several small objects: bronze and ivory statuettes of naked deities, a pendant representing a lion-headed eagle made of gold and lapis lazuli, metal bracelets, pins and pendants, cylinder seals made of shell, some amulets, and a multitude of beads of different size and shape, including one made of lapis lazuli engraved with the name of Mesanepada, ruler of Ur. The exceptionality and richness of this ensemble led its discoverer to interpret it as a treasure, probably buried in haste by its owner. This treasure, named the Treasure of Ur, is all the more precious since it was buried in the central area of the Sacred Precinct, which corresponds to the Holy Place of the sanctuary built within the palace.